MODERN VIEWS ON THE TREATMENT OF INGUINAL HERNIAS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The main forms of classification of inguinal hernias are described. The most reasonable classification of L. M. Nyhus inguinal hernias is presented, which allows comparing the results of hernioplasty performed by domestic and foreign authors. The history of traditional hernia repair techniques is reflected. Attention is focused on the most effective methods (Shouldice, Lichtenstein, endoscopic methods), which have gained worldwide fame and have significantly improved the quality of life of patients. It is indicated that the method of hernioplasty should be determined by the degree of destruction of the posterior wall of the inguinal canal (and the inner inguinal ring). It has been established that the extensive experience of hernia surgeries performed by foreign and domestic authors raises concerns about the implantation of synthetic materials that have a negative effect on the patient's quality of life.It is indicatedthat the search for new methods of reconstruction of the inguinal canal remains an urgent medical problem.